The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s1806-92902016000900009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of digestion of low-quality forage grazed by beef cattle fed supplements containing increasing levels of rumen undegradable protein

Abstract: -This experiment was conducted to evaluate the degradation kinetics and microbial efficiency of beef cattle grazing on low-quality forage and receiving supplements with different levels of rumen undegradable protein (RUP). The animals grazed on palisade grass pasture solely or this pasture and supplement containing 40 or 60 g of RUP per 100 g of crude protein (CP). The degradation profiles of neutral detergent fiber, fiber carbohydrates, and neutral detergent insoluble protein were interpreted kinetically by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The higher CP content observed in those pastures may be attributed to the greater participation of green and tender leaf blades in the forage canopy, due to the younger age of the plants (22.8 days) when compared with that of the plants managed at 30 days of defoliation. It is notable that diets with CP levels lower than 70 g/kg can cause an imbalance in rumen degradation and microbial synthesis (Van Soest, 1994;Gomes et al, 2016). In our study, as can be observed, CP values ranged between 141.27 (TZ95) and 119.91 (TZ30) g/kg DM (Table 1).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The higher CP content observed in those pastures may be attributed to the greater participation of green and tender leaf blades in the forage canopy, due to the younger age of the plants (22.8 days) when compared with that of the plants managed at 30 days of defoliation. It is notable that diets with CP levels lower than 70 g/kg can cause an imbalance in rumen degradation and microbial synthesis (Van Soest, 1994;Gomes et al, 2016). In our study, as can be observed, CP values ranged between 141.27 (TZ95) and 119.91 (TZ30) g/kg DM (Table 1).…”
Section: Resultssupporting
confidence: 64%
“…It should be stressed that pastures managed with 95% interception of the PAR will also provide larger quantities of fermentable carbohydrates, potentiating microbial synthesis (Andrade-Montemayor, Gasca, & Kawas, 2009). This results in a shorter retention time of the herbage in the rumen (Gomes et al, 2016), ultimately maximizing intake (Table 2) and animal performance (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Sugarcane is grown extensively in America, Africa, Asia, and Oceania on account of its ease of cultivation and outstanding production of green mass, which facilitate its use in ruminant feeding during the dry season (characterized by low rainfall and high temperatures), which results in a shortage of forage (Bento et al, 2018). Thus, sugarcane is an excellent option for farmers as it has advantages such as great nutritional value and forage production per area, concurring with the period of forage shortage compared to tropical forages (Gomes et al, 2016). However, sugarcane production in Brazil focuses on the sugar-energy industry rather than on animal nutrition, making selecting varieties with better nutritional value for animal feeding necessary (Carvalho et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane deserves some attention due to its nutritional limitations, such as low protein and mineral levels and low-quality fibrous fractions. Among the nutritional limitations, the fibrous fractions significantly impact feed digestion, and protein and minerals can be corrected by supplements (Gomes et al, 2016). Sugarcane constituents with high lignification are in the strongly recalcitrant rind (Maziero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is the second largest meat producer in the world, producing about 10.32 million tons in 2020 and exporting 2.7 million with revenues of US$ 7.7 billion (Abiec, 2021). About 90% of this meat comes from cattle finished on pasture, which can significantly impact animal production in countries with a tropical climate, such as Brazil, where the dry season, from May to September, affects the growth capacity and vigor of grasses, i.e., the nutritive value of the pasture (Gomes et al, 2016). For this reason, supplementary practices, such as silage use, are adopted to keep the herd fed, healthy, and productive, regardless of drought duration and intensity (Henriksson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%